2011
DOI: 10.1097/pec.0b013e3182259908
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Emergency Ultrasound in Pediatric Emergency Departments

Abstract: In our study sample, there is wide variation in the uses of EUS and the training pediatric emergency physicians receive in its use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 23 publications
2
31
0
3
Order By: Relevance
“…Emergency POCUS in Canadian PEM fellowship programs CJEM JCMU 2016;18 (6)this subject, and, in 2008, Chamberlain et al sent a survey to all U.S. pediatric emergency medical directors, fellowship directors, and graduating fellows. [14][15][16] In 2011, 53/60 (88%) of U.S. PEM programs responding to their survey offer some POCUS training to their fellows, 14 compared to 65% in 2006 15 and 56% of the Canadian programs in our study. A pediatric-specific POCUS curriculum is currently offered in only three (33%) of the Canadian PEM programs, which is similar to U.S. reporting 5 years ago.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Emergency POCUS in Canadian PEM fellowship programs CJEM JCMU 2016;18 (6)this subject, and, in 2008, Chamberlain et al sent a survey to all U.S. pediatric emergency medical directors, fellowship directors, and graduating fellows. [14][15][16] In 2011, 53/60 (88%) of U.S. PEM programs responding to their survey offer some POCUS training to their fellows, 14 compared to 65% in 2006 15 and 56% of the Canadian programs in our study. A pediatric-specific POCUS curriculum is currently offered in only three (33%) of the Canadian PEM programs, which is similar to U.S. reporting 5 years ago.…”
Section: Discussionmentioning
confidence: 61%
“…In the study by Chamberlain et al, FAST use was reported by fellows to be 93%. 16 In that same survey, 53% of responders (fellows, PDs, and medical directors) stated that POCUS was used for soft tissue evaluation in their ED, 37% stated its use for cardiac assessment, 9% for abdominal assessment, and 40% for procedural guidance. In our study, the vast majority of PEM fellows stated that POCUS was used for these indications "never," "rarely", or "sometimes" (36 fellows for musculoskeletal problems, 35 for cardiac, 39 for abdominal assessment, and 36 for procedural guidance).…”
Section: Discussionmentioning
confidence: 99%
“…Tras un estudio bibliográfico y legal exhaustivo, concluimos que no existen estudios que revelen una respuesta concreta y única, si bien hay múltiples referencias donde se muestra que los clínicos no especialistas en Radiología tienen resultados equiparables o mejores que los radiólogos, únicamente con pautas sencillas 3,4 . Proponemos por tanto una respuesta sencilla: la ecografía ha de realizarla quien tenga la capacidad, los conocimientos, la inmediatez y, sobre todo, aquel médico que vaya a proporcionar una mejor respuesta al problema clí-nico que se nos plantee, en el momento concreto.…”
Section: Colaboración Especialunclassified
“…[4][5][6][7] Knowledge translation-from guideline to practice-has always been an area in which the medical profession has grappled with limited success. If knowledge translation is the major issue, then it behooves us to make a concerted effort to address these issues on a large scale.…”
Section: Niranjan Kissoon MDmentioning
confidence: 99%
“…Regardless of the reasons, the marked variation in opinions and practice patterns of clinicians seen in this and other reports is not acceptable yet is widely tolerated. 4,5 Standing on neutral grounds and accepting marked variability in practice for common conditions are not options. We should accept that variability is anathema to good practice but refrain from suggesting remedies based on gut reactions because they may be at best useless and at worst harmful.…”
Section: Niranjan Kissoon MDmentioning
confidence: 99%